Intelligent Leisure Solutions - Hisrich, Robert D.; Ricaurte, Cristina (London : SAGE Publications Ltd, 2017)
Intelligent Leisure Solutions (ILS) is a group of five companies based in Brazil working to create, implement, and manage intelligent solutions. As a completely technology-based solutions company, ILS is unique in its approach to travel, real estate, technology, and sustainable tourism. With high growth in the tourism industry, ILSs founding entrepreneur, Robert Phillips, is working to find the most appropriate, innovative growth strategy for expansion and sustainability of the business.
Originally published in Hisrich, R. (2015). Intelligent Leisure Solutions. In International entrepreneurship: Starting, developing, and managing a global venture (3rd ed., pp. 252271). Thousand Oaks: SAGE Publications, Inc. Print. ISBN: 9781483344393.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Intelligent Leisure Solutions; Strategic planning -- Brazil; Business planning -- Brazil